KEANEKARAGAMAN EKOLOGI HUTAN PADA KAWASAN HUTAN SUAKA MARGASATWA BUTON UTARA (SMBU) DI DESA EELAHAJI KECAMATAN KULISUSU - Kahirun Kahirun; La Baco S.; Nasaruddin Nasaruddin; Lukman Yunus (Universitas Haluoleo, 2019)
The forest area of SMBU is the largest conservation forest area in Southeast Sulawesi, located in the Buton archipelago, has many potential of forests that have abundant diversity. However, in line with the development of population andregional development, there has been a disruption to the forest area in the form of illegal logging. This has an impact on the decreasing diversity of forest vegetation in the region. The aim of the study was to analyze species richness and abundance as an indicator of the ecological diversity of forests in the forest area of the SMBU. Plant species measurement data are used to calculate the frequency, density, dominance and importance value index of vegetation, while analyzing the ecological diversity of forest vegetation with the calculation model using the diversity index method, species richness index and similarity index. The results showed that some species had the highest density, frequency and dominance at the tree spesies, namely the Holea (Cleistanthus sp), Redwood (Shorea spp) and Guava (Syzygium spp). At the pole level there are types of Guava (Syzygium spp), and Wukumalampa (Polyalthia lateriflora). While at the saplings level, guava (Syzygium spp) is found. Diversity index values at tree level, pole and saplings can be categorized as having decreased compared to the results of previous studies. The abundance of species shows that there is a tendency for the lower vegetation structure at the level of the pole and saplings to be less abundant. Keywords: forest area, northern buton wildlife reserve, forest structure, ecological diversity, diversity index